Immunoregulatory Mechanisms of Interferon - Hermann Fritz, Jorg; Duerr, Claudia U. (Frontiers Media SA, 2020)
Interferons (IFN) belong to the family of cytokines and have been described first in the late 1950s as an inhibitory factor of viral replication. Since then, the impact of interferon has been greatly expanded and its function comprises a role not only in different types of infection, cancer and autoimmunity but importantly also in immunehomeostasis. IFN have important anti-viral effects but it is becoming more and more evident that they are true immunomodulators and have an important impact on the development and maintenance of innate and adaptive immunity.